Infection of Animals With the Influenza Virus After a Preliminary Administration of the Preparation â€œCryocell-Haemocordâ€. Report I. Investigation of Functional Activity of Murine Immunocompetent Organs - Onasenko, Ye. S.; Brovko, Ye. V.; Volina, V. V.; Ponomareva, V. L. (Problems of Cryobiology and Cryomedicine, 2010)
It was established that a long prophylactic effect, which provided immunity of the animals investigated to the influenza virus for 6 months after the intranasal administration of the preparation â€œCryocell-haemocordâ€, was observed. A stimulating effect of the preparation on the mouse immunocompetent organs before and after the influenza virus infection was revealed. A prophylactic administration of the preparation delays the rate of virus replication. A further research on mechanisms of the anti-virus effects of the preparation â€œCryocell-haemocordâ€ is of great interest.